Review of best treatment option in heart failure 2023 - Santiago, Gerardo Garcia; Gomez, Andrea Marin; Gonzalez, Guillermo Avalos; Ramos, Oscar Jesus Leal; Castro, Alejandra Arias; Pere, Mariano Belisario López (International Journal of Advances in Medicine, 2023)
Congestive heart failure is a clinical condition in which the heart is unable to pump enough blood to meet the metabolic needs of the body because of pathological changes in the myocardium. The three main causes of CHF are coronary artery disease, diabetes mellitus, and hypertension. US hospitalizations for heart failure decreased up until 2012; however, from 2013 to 2017, an increase in HF hospitalizations was observed. In 2017, there were 1.2 million HF hospitalizations in the United States among 924 000 patients with HF. This represents a 26% increase in HF hospitalizations and number of patients hospitalized with HF. For this reason, as a team, we have decided to conduct a review of the best treatment options for heart failure based on multiple articles.